The population genetic structure of Rhizoctonia solani AG-3PT from potato in the Colombian Andes - Ferrucho, Rosa L.; Ceresini, Paulo C. [UNESP]; Ramirez-Escobar, Ursula M.; McDonald, Bruce A.; Cubeta, Marc A.; García-Domínguez, Celsa (Scientific Societies, 2013)
The soilborne fungus Rhizoctonia solani anastomosis group 3 (AG-3PT) is a globally important potato pathogen. However, little is known about the population genetic processes affecting field populations of R. solani AG-3PT, especially in the South American Colombian Andes, which is near the center of diversity of the two most common groups of cultivated potato, Solanum tuberosum and S. phureja. We analyzed the genetic structure of 15 populations of R. solani AG-3PT infecting potato in Colombia using 11 simple-sequence repeat (SSR) markers. In total, 288 different multilocus genotypes were identified among 349 fungal isolates. Clonal fractions within field populations were 7 to 33%. R ST statistics indicated a very low level of population differentiation overall, consistent with high contemporary gene flow, though moderate differentiation was found for the most distant southern populations. Genotype flow was also detected, with the most common genotype found widely distributed among field populations. All populations showed evidence of a mixed reproductive mode, including both asexual and sexual reproduction, but two populations displayed evidence of inbreeding. © 2013 The American Phytopathological Society.
Keywords: fungal DNA; microsatellite DNA; Colombia; genetic variability; genetics; genotype; geography; Hyphomycetes; isolation and purification; microbiology; plant disease; polymerase chain reaction; population genetics; potato; DNA, Fungal; Genetic Structures; Genetic Variation; Genetics, Population; Genotype; Geography; Microsatellite Repeats; Plant Diseases; Polymerase Chain Reaction; Rhizoctonia; Solanum tuberosum